Investigation of changes in structural properties of polycrystalline ln0.6628Ga0.3372N thin film - Mantarcı, Asım (My University, 2021)
Abstract: In 0.6628Ga 0.3372N thin film was coated on GaN/n-Si (100) under various powers. Optical properties, crystal structure, bonding properties, chemical composition, phonon modes, and morphological properties of the thin films were experimentally characterized by UV, XRD, XPS, AFM, and Raman. Crystallite sizes of the thin film for (011) and (110) orientations were ranging from ~ 7 to 12 nm and ~8 to 15 nm with error 0.2 nm, and they had a slightly rising trend with increasing powers. Increasing power gave rise to a decrease in the optical band gap (direct-allowed) (from 2.22 to 2.18 eV) mainly due to the increasing crystallite sizes of the thin film. The refractive index value of the thin film showed an increasing trend with increasing power for many physical models. XPS analyses confirmed that the film had In2O3 bond, InNxOy bond, In-N bond, Ga–N bond, Ga-O bond, Ga metallic with different quantities. Raman results gave characteristic A1(LO) longitudinal optical phonon mode and E2(high) optical phonon mode of InGaN, complied with other results. Basically, changes in some physical properties of thin film under varying power were discussed. Graphic abstract: [Figure not available: see fulltext.] © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.
Keywords: Crystal structure; Nitrides; Physical vapor deposition; Thin film coating; X-ray diffraction